Repellent effect of neem oil (Azadirachta indica A. Juss) against mosquitoes (Anophelex spp) in piglets - Llanos Gonzáles, Andrea (2020)
The aim of this study was to evaluate the repellent efficacy for mosquitoes (Anophelex spp) of three doses of neem oil (Azadirachta indica A. Juss) in pigs under field conditions. The research was carried out at a time of year of abundance of mosquitoes in Tumbes, Peru. Forty recently weaned piglets were used, 10 per treatment, kept in indoor cages protected against mosquitoes. For the field test, four piglets per day were exposed randomly in external cages without protection to the mosquito (a different animal for each treatment per day) for 14 days over a period of two months. Neem oil was extracted with the soxhlet apparatus and the formula included 30% glycerin, 1, 2 or 3% neem oil (T1, T2, T3, respectively), and taken to 100% with pharmaceutical alcohol. A dose of 50 ml/piglet distributed throughout the body was applied. The bites and the number of mosquitoes were evaluated on four occasions of 15 minutes for three hours per day (06:15, 07:00, 07:45, 08:30) with intervals of 30 minutes of protection to the piglets. The mosquitoes biting the piglets (red abdomen) were collected using manual vacuum cleaners. The neem oil yield was 43.25 ± 1.64%. The percentage of repellency was 88.74 ± 37.8, 75.66 ± 122.8 and 52.27 ± 164.6% for T1, T2 and T3, respectively (p<0.05). The percentage of protection (repellent efficiency) was 93.92 ± 125.3, 85.71 ± 56.8 and 67.78 ± 13.4% for T1, T2 and T3, respectively (p<0.05). The average number of mosquitos in the control group, T0 (without repellent dose) was 365.54 ± 418 386 bites/day, being different (p<0.05) to the treated groups T1, T2 and T3 (49.98 ± 7940.15; 113.82 ± 40 382; 19.52 ± 1184 bites/day, respectively, and without significant difference between the treated groups. The Repellency Index (IR) for T1, T2 and T3 was 0.47, 0.24 and 0.10, respectively, which shows that the dose used in T3 showed a higher level of repellency and efficacy against mosquitoes.